Tea polyphenol EGCG ameliorates obesity-related complications by regulating lipidomic pathway in leptin receptor knockout rats - Guohuo Wu; Huijun Cheng; Huimin Guo; Zhuang Li; Daxiang Li; Zhongwen Xie (2023)
Tea polyphenol epigallocatechin-3-gallate (EGCG) has been widely recognized for antiobesity effects. However, the molecular mechanism of lipidomic pathway related to lipid-lowering effect of EGCG is still not well understood. The aim of this study was to investigate the effects and mechanism of EGCG activated hepatic lipidomic pathways on ameliorating obesity-related complications by using newly developed leptin receptor knockout (Lepr KO) rats. Results showed that EGCG supplementation (100 mg/kg body weight) significantly decreased total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) levels both in the serum and liver, and significantly improved glucose intolerance. In addition, EGCG alleviated fatty liver development and restored the normal liver function in Lepr KO rats. Liver lipidomic analysis revealed that EGCG dramatically changes overall composition of lipid classes. Notably, EGCG significantly decreased an array of triglycerides (TGs) and diglycerides (DGs) levels. While EGCG increased 31 glycerophospholipid species and one sphingolipid species levels, such as phosphatidylcholines (PCs), phosphatidylethanolamines (PEs), phosphatidylserines (PSs) and phosphatidylinositols (PIs) levels in the liver of Lepr KO rats. Moreover, 14 diversely regulated lipid species were identified as potential lipid biomarkers. Mechanistic analysis revealed that EGCG significantly activated the SIRT6/AMPK/SREBP1/FAS pathway to decrease DGs and TGs levels and upregulated glycerophospholipids synthesis pathways to increase glycerophospholipid level in the liver of Lepr KO rats. These findings suggested that the regulation of glycerolipids and glycerophospholipid homeostasis might be the key pathways for EGCG in ameliorating obesity-related complications in Lepr KO rats.